2022
DOI: 10.3390/jpm12091435
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in Difficult Asthma: The Need for Personalised and Non-Pharmacological Approaches to Address a Difficult Breathing Syndrome

Abstract: Three to ten percent of people living with asthma have difficult-to-treat asthma that remains poorly controlled despite maximum levels of guideline-based pharmacotherapy. This may result from a combination of multiple adverse health issues including aggravating comorbidities, inadequate treatment, suboptimal inhaler technique and/or poor adherence that may individually or collectively contribute to poor asthma control. Many of these are potentially “treatable traits” that can be pulmonary, extrapulmonary, beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 144 publications
1
8
0
Order By: Relevance
“…Comorbidity in difficult asthma is strongly associated with poorer asthma control, greater symptom burden, frequent exacerbations, mOCS dependency and non-adherence to asthma treatment. [29][30][31]33,34 We found that severity of comorbidities based on questionnaire scores was lower and HRQoL was better in mild asthma compared to difficult disease. To et al found 6% of hospitalisations were related to asthma and asthma comorbidity in their population-based cohort study of 12 million residents in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Comorbidity in difficult asthma is strongly associated with poorer asthma control, greater symptom burden, frequent exacerbations, mOCS dependency and non-adherence to asthma treatment. [29][30][31]33,34 We found that severity of comorbidities based on questionnaire scores was lower and HRQoL was better in mild asthma compared to difficult disease. To et al found 6% of hospitalisations were related to asthma and asthma comorbidity in their population-based cohort study of 12 million residents in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 75%
“…It has recently been proposed that we shift our focus to the concept of complex asthma as a multimorbidity “Difficult Breathing Syndrome” rather than a severe asthma-centric state, recognising the constellation of conditions with multiple “treatable traits” contributing to difficult asthma. 34 Whether such notions are relevant to mild asthma too is worth consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The potential association between bronchial obstructive disorders and MS has acquired profound significance in this context. MS comprises several pathological conditions, conferring this association a unique and noteworthy character [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most asthmatic patients have multiple comorbidities including rhinitis, sinusitis with or without nasal polyps, airway infections, gastro-esophageal reflux disease, obesity, sleep-related breathing disorders, anxiety and depression, and polycystic ovary syndrome (PCOS). Adequate treatment of comorbidities is essential to achieve satisfactory asthma control [ 8 ].…”
Section: Introductionmentioning
confidence: 99%